Pemberdayaan Guru SMK Melalui Kurikulum Digital dan Teknologi CAD/CAM Berbasis Design for Manufacturing (DfM) pada Praktikum Pemesinan di SMK MedikaCom Bandung - Arliyanto, P Yudi Dwi; Rivandi, Merdieco; Sari, Marta Hayu Raras Sita Rukmika; Yushardian, Hamdi Akmal; Wibowo, Rifky Budiarto; Yusuf, Rifqi Akmal; Shandra, Olivia Ferisca; Debora, Fransisca; Arridho, Ilham Ali; Khoerunnisa, Ahshonat; Setiawan, Aan Eko; Amhar, Usamah (Jurnal SOLMA, 2025)
Background: Vocational education plays a crucial role in preparing competent graduates who meet industry needs. SMK MedikaCom Bandung, as a Center of Excellence school, continuously strives to enhance teacher competencies to improve the quality of graduates who can be absorbed into the workforce and to serve as a model for other vocational schools. The Department of Mechanical Engineering at SMK MedikaCom Bandung seeks to strengthen both teacher and student understanding of CAD/CAM technology through the application of CNC machines, supported by training and the integration of a (DfM)-based curriculum. Methods: The activities were conducted on August 22 and 27, 2025, through several stages, including socialization, FGDs, teacher training on DfM, development of digital teaching modules, and student mentoring in product-based projects. Evaluation was carried out using pre- and post-test instruments to measure differences in participants’ knowledge and skills before and after the program. Results: The test results indicated that all variables had p-values < 0.05, signifying a significant improvement. Teachers showed an increase in their understanding of CAD/CAM applications on CNC machines from 80% to 90% and in their knowledge of Project-Based Learning (PjBL) and Teaching Factory methods from 70% to 85%. Students also demonstrated improved comprehension of CNC utilization in non-conventional machining learning from 75% to 93%. Conclusions: The community service program effectively enhanced teachers’ and students’ mastery of CAD/CAM technology and their understanding of DfM. These outcomes support the implementation of an industry-based digital curriculum and strengthen the relevance of vocational school learning to workforce demands.